Immune Cells Profiles In The Peripheral Blood Of Patients With Moderate To Severe COVID-19 And Healthy Subjects With and Without Vaccination With The Pfizer-BioNTech mRNA Vaccine - Al-Attiyah, Raja’a; Safar, Hussain A.; Botras, Lotfy; Botras, Marina; Al-Kandari, Fatma; Chehadeh, Wassim; Mustafa, Abu Salim (Frontiers in Immunology, 2022)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), the causative agent of Coronavirus disease 2019 (COVID-19), has caused a global crisis. Patients with COVID-19 present with a range of clinical manifestations, from no symptoms to severe illness. However, little is known about the profiles of immune cells required to protect against SARS-CoV-2. This study was performed to determine the immune cells profiles in the peripheral blood of COVID-19 patients with moderate to severe disease (n=52), and compare the findings with those from healthy subjects vaccinated with Pfizer BioNTech mRNA vaccine (VS) (n=62), and non-vaccinated healthy subjects (HS) (n=30) from Kuwait. Absolute counts and percentages of total lymphocytes and lymphocyte subsets (CD3+ T cells, CD4+ T cells, CD8+ T cells, CD19+ B cells, and CD16+CD56+ NK cells) in the peripheral blood of the three groups were analyzed using flow cytometry. The results showed that the absolute counts of total lymphocytes, CD3+, CD4+, and CD8+ T cells, CD19+ B cells, and CD56+ NK cells, were significantly lower in COVID-19 patients than normal healthy controls and vaccinated subjects. The percentages of CD3+ and CD4+ T lymphocytes were also significantly lower in the COVID-19 patients. However, the percentage of CD16+CD56+ NK cells was significantly higher in the peripheral blood of COVID-19 patients, compared to the HS and VS groups with no detectable differences in the percentages of CD8+ T cells and CD19+ B cells between the three groups. Analysis of the monocyte subsets has showed a significantly higher percentage of CD14+HLA-DR+ monocytes in COVID-19 patients compared to HS whereas the inflammatory CD14+CD16+ HLA-DR+ monocytes, and the non-classical CD16+HLA-DR+ monocytes showed significantly lower frequency in the blood of the patients than that of HS. These findings demonstrate perturbations of both innate and adaptive immune cell subsets that reflect dysregulated host responses in COVID-19 patients with moderate to severe disease.